Qualitative and structural analysis of the managerial competency of future physical education and sport specialists - Dubrevskiy, Y.M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: identifying theoretical and practical communication management competence in vocational training of future specialists of physical education and sport. Material: analysis of 220 literary sources of psycho-pedagogical nature, sports theory, control theory, methods of physical education, which cover the administrative aspect of modern specialist training. Results: the need to form a managerial competency in the process of future specialists in education and sport preparation with regard to its qualitative and structural characteristics was established in the research. Conclusions: there is an evidence that the meaningful impact on the development of managerial competency takes place successfully under conditions of personal socialization in the communicative environment; orientation towards systematic assimilation of knowledge about the phenomenon of management, focus on the effective implementation of activities; development of professional and individual characteristics, which together meet the objectives and content of the pedagogical preparation of students.